ASSISTANCE IN THE DEVELOPMENT OF ASSESSMENT INSTRUMENTS FOR DIFFERENTIATED LEARNING IN THE MERDEKA CURRICULUM FOR SPECIAL EDUCATION TEACHERS IN BANTEN PROVINCE - Abadi, Reza Febri (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2024)
Four issues have been identified as requiring solutions, Teachers encounter difficulties in developing disability assessment instruments for differentiated learning in the Merdeka Curriculum. There is a lack of understanding of how to assess disabilities for differentiated learning in the independent curriculum. Teachers lack the necessary competence to carry out assessment procedures for students with disabilities. There is a lack of cooperation between teachers and other institutions. Prior to the provision of assistance, observations were conducted to ascertain the requisite needs, thereby enabling the design of an efficacious programme. Furthermore, an Assessment Instrument Book for Students with Disabilities was devised as a technical guidance material. The mentoring process is conducted intensively with teachers in the construction of assessment instruments for students with disabilities. The results obtained subsequent to the implementation of technical guidance encompass a multitude of aspects, including augmented knowledge and practical skills amongst the participants.